1999
DOI: 10.1021/es981217k
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Trichloroethylene in an Artificial Aquifer with Trees:  A Controlled Field Study

Abstract: Poplar trees have been evaluated in the field for the control of contaminated groundwater movement, but to date, the fate of the contaminants has not been demonstrated. In the present study, we tested a hybrid poplar for the uptake and degradation of trichloroethylene (TCE). Plants were exposed to TCE-contaminated groundwater under field conditions in lined cells for three years. During the growing seasons, the trees were able to remove over 99% of the added TCE. Less than 9% of the TCE was transpired to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 13 publications
6
65
0
1
Order By: Relevance
“…Because it has been previously demonstrated that hybrid cottonwood, another kind of poplar, can remove TCE from hydroponic solution (3,18,19), the poor performance of the nontransgenic hybrid poplar in this study was unexpected. However, the hybrid cottonwood (Populus trichocarpa ϫ Populus deltoides) studies were done by using rooted cuttings in flasks with the foliage in open air or in field trials with full-grown trees, whereas this study was conducted with unrooted poplar (Populus tremula ϫ Populus alba) cuttings in sealed vials.…”
Section: Discussionmentioning
confidence: 78%
“…Because it has been previously demonstrated that hybrid cottonwood, another kind of poplar, can remove TCE from hydroponic solution (3,18,19), the poor performance of the nontransgenic hybrid poplar in this study was unexpected. However, the hybrid cottonwood (Populus trichocarpa ϫ Populus deltoides) studies were done by using rooted cuttings in flasks with the foliage in open air or in field trials with full-grown trees, whereas this study was conducted with unrooted poplar (Populus tremula ϫ Populus alba) cuttings in sealed vials.…”
Section: Discussionmentioning
confidence: 78%
“…Previous work with untransformed poplar trees has shown that chlorinated hydrocarbons such as TCE are taken up along with the water transpired (14). There is little selective uptake of TCE from groundwater; therefore, reductions in the concentration of TCE are insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have been shown to take up and, in some cases, to metabolize organic pollutants (6), excess nutrients (6, 7), 2,4,6-trinitrotoluene (TNT) (8,9), and metals (10,11). Work in our laboratory has demonstrated that poplar trees are able to take up and metabolize TCE both under laboratory conditions and in a field test (12)(13)(14).…”
mentioning
confidence: 88%
“…The halogenated solvent trichloroethylene (TCE; log K ow = 2.42) is metabolized by cultured cells of poplar (Populus spp.). [42] Newman et al [43] showed remediation of TCE in a controlled field study. Nzengung and Jeffers [14] identified four phytoprocesses involved in the plantmediated transformation of chlorinated organic compounds: www.chemsuschem.org 1) rapid sequestration by partitioning to the lipophilic plant cuticles, 2) phytoreduction to less chlorinated metabolites, 3) phytooxidation, and 4) assimilation into the plant tissue as non-phytotoxic products.…”
Section: Substrate Characteristicsmentioning
confidence: 99%